Examining the Efficacy of Conjoint Behavioral Consultation for Middle School Students With Externalizing Behavior Problems. (November 2020) - Garbacz, S. Andrew; Beattie, Tiffany; Novotnak, Tanya; Kurtz-Nelson, Eva; Zahn, Miranda; Yim-Dockery, Huna; Cohenour, Jessica; Jordan, Phoebe
This exploratory study examined the efficacy of Conjoint Behavioral Consultation for addressing classroom disruptive behavior for middle school students with externalizing behavior problems. In addition, the parent–teacher relationship, parent and teacher competence in problem-solving, and acceptability were examined. Participants were parents and teachers of four middle school students with externalizing behavior problems. Disruptive classroom behavior data were examined in a concurrent multiple baseline across participants design. Parent–teacher relationship, competence in problem-solving, and acceptability data were examined descriptively. Findings suggested improvements in disruptive behavior for each participant. However, limitations impeded interpretations. Parent–teacher relationship data were inconclusive. Six out of eight parents and teachers with pretest and posttest data reported improvements in their competence in problem-solving. All parents and teachers perceived the consultation process favorably. Limitations and future directions are discussed.